The effect of algoritmics government, artificial intelligence, and tax service on tax compliance - Akbari Adha; Rulinawaty Rulinawaty; Faizal Madya (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Taxes are an essential pillar of countries and nations. It contributes to the country's economic growth and support for sustainable development. Therefore, this study aims to investigate the effect of algorithmic government, artificial intelligence, and tax services on tax compliance. This research uses a quantitative approach with a survey method. The sample was 393 taxpayers. The research instrument used was a questionnaire designed on a Likert scale with five response options. The questionnaire was distributed via the WhatsApp application and email in Google Form format. Data were analyzed using regression. The results found that algorithmic government, AI, and tax services, partially and simultaneously, affect tax compliance among taxpayers. These findings provide insight into how tax compliance can be improved through algorithmic government, AI, and tax services. Therefore, researchers and practitioners can discuss the findings of this research critically and in depth before adapting and adopting them in their future work without ignoring the limitations of this research.